AETIOPATHOLOGICAL ANALYSIS OF BLINDNESS WITH SPECIAL REFERENCE TO ANATOMICAL LOCATION – A CLINICAL STUDY - Dr.V.Murali Krishna M.S, Dr.A.Sharmil, Dr.A.P.R.Naidu M.S Dr.V.Satya Srinivas M.S (International Journal of Scientific Research and Management (IJSRM), 2015)
Blindness is very common. The World Health Organization says that around 161million people have at least some degree of “visual impairment”, of whom 37 million are blind. There are many causes of blindness, including infections, malnutrition, injury, and ageing. Around 90% of blind people live in developing countries. Surveys to find this out are important as a first step toward providing prevention and treatment services. Surveys play an essential part in international efforts to fight blindness